The Efficacy of ChatGPT in academic outputs of fourth-year BSIT students at Leyte Normal University - Bula, Marian Jake; Sequito, Alex Gabrielle Marri; De Paz, Kenneth (Journal of Education and Society, 2025)
Abstract With the recent introduction of the ChatGPT, a lot of remarks and conjectures were made on the possible facets of society that this AI revolution might benefit. The education field is one of the primary domains affected by ChatGPT, the impact to BSIT students remains yet to be fully understood. Investigating the impact of ChatGPT on the academic experiences of fourth year BSIT students becomes paramount to explore its influence on the students’ academic outputs. The study used descriptive research design to obtain data through survey questionnaires to provide the researchers with more precise information needed in the study. Moreover, the researchers utilized a survey questionnaire using purposive sampling. The findings showed that ChatGPT is a useful AI tool for improving students' academic outputs, especially in programming-related activities such as debugging, code optimization, and understanding code snippets.